2019
DOI: 10.3390/met9040408
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of AA6012 Aluminum Alloy Processed by ECAP and Cryogenic Treatment

Abstract: In this work, the corrosion behavior of an AA6012 aluminum alloy, submitted to a T6 strengthening treatment (solubilization and aging), and later to a severe plastic deformation, through equal channel angular pressing (ECAP) was studied. Some of these samples were submitted to a cryogenic treatment before the ECAP process. The analysis of corrosion behavior of the AA6012 samples was carried out at room temperature by means of electrochemical characterization in 0.1 M Cl− deaerated and aerated solution at pH 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In this respect, previous works by one of these authors showed that the different strain paths to which tempered aluminum alloys can be subjected by ECAP are able to effectively influence the secondary-phase precipitates volume fraction [65,66]. Indeed, this did not induce a marked deterioration of other important properties such as corrosion resistance, as reported by Vicerè et al [67,68]. In ECAP, samples are usually in form of cylindrical or square-section rod billets that are continuously forced to follow a linear path into a L-shaped equal-channel [69][70][71][72][73][74][75][76][77][78].…”
Section: Introductionmentioning
confidence: 57%
“…In this respect, previous works by one of these authors showed that the different strain paths to which tempered aluminum alloys can be subjected by ECAP are able to effectively influence the secondary-phase precipitates volume fraction [65,66]. Indeed, this did not induce a marked deterioration of other important properties such as corrosion resistance, as reported by Vicerè et al [67,68]. In ECAP, samples are usually in form of cylindrical or square-section rod billets that are continuously forced to follow a linear path into a L-shaped equal-channel [69][70][71][72][73][74][75][76][77][78].…”
Section: Introductionmentioning
confidence: 57%
“…8. The inductive element is not used in the EEC to curve fit the EIS data because the inductive loop is not well defined and the curve fitting of the inductive character observed in the present EIS data will not yield the appropriate information, hence the typical Randle circuit is used to fit the only capacitive loop [36]. The corrosion parameters attained from curve fitting of EIS data are tabulated in Table 3.…”
Section: Electrochemical Corrosion Analysismentioning
confidence: 99%
“…In the used EEC, Rs represents the solution resistance, the RC couple denotes the charge transfer resistance Rct and the double layer constant phase element Qdl (i.e., double layer capacitance which forms at the working electrode/electrolyte interface because of the adsorbed ions on the working electrode surface) [35,36]. The constant phase element exponent 'n' value obtained from EEC analysis is less than '1' and it may due to the surface roughness created from the adsorbed corrosion products on the working electrode.…”
Section: Electrochemical Corrosion Analysismentioning
confidence: 99%
“…The ECAP processes for Al alloys are significantly interesting in the automotive, aerospace, and building industries. Exceptional mechanical [15][16][17][18][19][20][21] and electrochemical properties [21][22][23][24][25][26][27] are observed in Al alloys because of ECAP.…”
Section: Introductionmentioning
confidence: 99%